2000
DOI: 10.1002/1098-2752(2000)20:5<252::aid-micr5>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications of native arteriovenous fistulas for hemodialysis: Role of microsurgery

Abstract: This article describes the treatment of 56 early and late vascular complications of native arteriovenous fistula (AVF) in patients with end-stage renal disease, between January 1987 and January 1999. Twenty-six were arteriovenous aneurysms and 2 pseudoaneurysms; 25 were thromboses. We also observed two cases of periarteritis associated with systemic lupus erythematosus (SLE) and one complex iatrogenic lesion caused by an attempt at percutaneous restoration of potency. We applied microsurgical principles, instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Comparing both types of aneurysms, it can be concluded that this patient had a true aneurysm, based on the size of dilation which is three times larger than native size (over 2 cm) [19]. Patients who experience AVF aneurysm have additional risk factors which include hypertension, hypotension, immunologic disease, diabetes mellitus, arteriolosclerosis, early puncture of AVF site, repeated punctures, and mechanical compression [20,21]. True aneurysm; however take years to occur after fistula creation, with a mean time of 47 months [19].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing both types of aneurysms, it can be concluded that this patient had a true aneurysm, based on the size of dilation which is three times larger than native size (over 2 cm) [19]. Patients who experience AVF aneurysm have additional risk factors which include hypertension, hypotension, immunologic disease, diabetes mellitus, arteriolosclerosis, early puncture of AVF site, repeated punctures, and mechanical compression [20,21]. True aneurysm; however take years to occur after fistula creation, with a mean time of 47 months [19].…”
Section: Discussionmentioning
confidence: 99%
“…AVF aneurysms are associated with a high rate of complications, such as stenosis, thrombosis, and infection [3]. Consequently, it is essential to manage VARAs to preserve VA, but they are difficult to salvage, and conservative management can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney replacement therapies for patients with end-stage renal failure include peritoneal dialysis, hemodialysis and kidney transplantation [1]. Creating an arteriovenous fistula (AVF) requires surgeon skill and experience, but provides comfort and safety for the patient [2,3]. Creating an autologous AVF for hemodialysis patients is considered the best treatment method [4].…”
Section: Introductionmentioning
confidence: 99%
“…Large differences in the frequency of complications in some studies also indicate differences in the frequency of some risk factors. In addition to demographic characteristics of patients, the occurrence of certain complications depends on the underlying kidney disease, the presence of comorbid conditions or various metabolic and immune disorders that occur in chronic renal failure and have already been mentioned in the pathogenesis of AVF stenosis and thrombosis [7,8,28]. Recently, Gardeezi et al [35] have shown that low concentration of 25(OH)D and high concentration of FGF-23 and parathormone were associated with a higher risk for AVF reinterventions.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Differences in the frequency of each complication can be explained by differences in surgical technique, AVF localization, diagnostic methods, but, above all, differences in the characteristics of patients and the quality of their blood vessels. It has been described that the age of patients, sex, underlying disease, comorbidities, but also the use and care of AVF significantly affect the occurrence of complications and survival of AVF [4,8,16].…”
Section: Introductionmentioning
confidence: 99%